2009
DOI: 10.3201/eid1512.090487
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Epidemiology of Tularemia Outbreaks in Sweden

Abstract: Transmission sites of specific Francisella tularensis genotypes were highly localized during natural outbreaks of human tularemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
73
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 23 publications
(43 reference statements)
17
73
0
2
Order By: Relevance
“…The range of arthropod vectors connected with tularemia has expanded to include ticks [19,40,[53][54][55][56][57][58][59][60], mosquitoes [56,61], horse flies [56], fleas [62] and gamasid mites [3]. In Europe, much of the research on the role of arthropod vectors in the transmission of F. tularensis subsp.…”
Section: Tularemia In Vectorsmentioning
confidence: 99%
“…The range of arthropod vectors connected with tularemia has expanded to include ticks [19,40,[53][54][55][56][57][58][59][60], mosquitoes [56,61], horse flies [56], fleas [62] and gamasid mites [3]. In Europe, much of the research on the role of arthropod vectors in the transmission of F. tularensis subsp.…”
Section: Tularemia In Vectorsmentioning
confidence: 99%
“…Recent studies in Sweden have indicated phylogeographical patterns both in local outbreaks and across larger geographical distances. These studies from Sweden also identified areas where F. tularensis persisted over several years and spatial associations of certain genetic subpopulations [16]. Little is known about phylogeographical patterns of F. tularensis in Norway.…”
Section: Introductionmentioning
confidence: 99%
“…These pathogens may cause anthrax, tularemia, plague, brucellosis, glanders, melioidosis, and Q fever, respectively. In most parts of the world, the natural prevalence of these agents is low, even though some of these agents cause outbreaks in human and animal populations from time to time (5)(6)(7)(8). The intentional release of these agents, however, can result in severe public health consequences, as was shown in the Unites States in 2001 (9,10).…”
mentioning
confidence: 99%